Aprostocetus (Ootetrastichus) infulatus (Hymenoptera: Eulophidae): description of the male, new distribution and first host records - Albarracin, Erica Luft; Triapitsyn, Serguei V. (Zootaxa, 2007)
The large and cosmopolitan genus Aprostocetus Westwood (Hymenoptera: Eulophidae: Tetrastichinae) currently includes 697 valid species (Noyes 2003). In the Neotropical region there are 52 described species of Aprostocetus, three of which belong to the subgenus Ootetrastichus Perkins. Species of A. (Ootetrastichus) are external egg parasitoids (acting as egg predators) of Hemiptera (Cicadellidae and Delphacidae), Orthoptera (Gryllidae), Odonata, and Coleoptera (Dytiscidae) (Clausen 1940; Graham 1987; Noyes 2003).